2018
DOI: 10.1002/jcp.26783
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite induces apoptosis via ROS‐mediated NF‐κB signaling and activation of the Bax–caspase‐9–caspase‐3 axis in 4T1 cells

Abstract: Sodium selenite (SSE), a source of inorganic selenium, has been widely used as a clinical cancer treatment, but the precise molecular mechanisms of SSE remain to be elucidated. Our in vitro experiments have confirmed that SSE treatment causes a transient increase in intracellular reactive oxygen species (ROS) levels, resulting in the inhibition of nuclear transcription factor-κB (NF-κB) signaling and p65 and nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha phosphorylation lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 49 publications
1
42
0
Order By: Relevance
“…They can specifically recognize pathogen‐related molecules, and induce and activate inflammatory factors such as NF‐κB and IFN, and mediate various inflammations such as IL‐1β, IL‐6, and TNF‐α. NF‐κB plays a central role in the transcriptional regulation of much cell‐stimulated cell information, involves in the expression and regulation of various genes, and is a hallmark of activations of cells (Zhang et al, ). In addition, studies have shown that peiminine acts as an anti‐inflammatory agent by inhibiting the activation of the AKT/NF‐κB signaling pathway (Gong, Li, Ma, Guo, & Kan, ).…”
Section: Discussionmentioning
confidence: 99%
“…They can specifically recognize pathogen‐related molecules, and induce and activate inflammatory factors such as NF‐κB and IFN, and mediate various inflammations such as IL‐1β, IL‐6, and TNF‐α. NF‐κB plays a central role in the transcriptional regulation of much cell‐stimulated cell information, involves in the expression and regulation of various genes, and is a hallmark of activations of cells (Zhang et al, ). In addition, studies have shown that peiminine acts as an anti‐inflammatory agent by inhibiting the activation of the AKT/NF‐κB signaling pathway (Gong, Li, Ma, Guo, & Kan, ).…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain the cytotoxicity of the samples, we detected apoptosis by using Annexin V‐FITC and PI as stains . After treatment of Hela cells with different concentrations of GO‐CO‐ γ ‐PGA‐DOX for 24 h, the number of apoptotic cells increased in a concentration dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…At this stage, the underlying mechanism of action of these novel selenoesters against C. glabrata is unknown and more experiments are needed to determine the ultimate mechanism behind the antifungal activity described herein. Selenocompounds and among them, selenoesters, as briefly mentioned in the introduction [31][32][33][34][35][36][37][38][39], have been proven in previous works to be able to exert a wide range of interesting biological activities, both in the anticancer and The effect of Se-8 on the formation of biofilms generated by C. glabrata dental isolates at t = 0 or 24 h and 4 µg/mL was very weak (0.15 ± 0.03-0.80 ± 0.08 BBU, and 0.07 ± 0.03-0.51 ± 0.14 BBU, respectively), compared to caspofungin (0.93 BBU ± 0.03, 0.56 ± 0.17 BBU, respectively), being statistically significant, p < 0.0001. Selenocompound had the lowest biofilm-reducing effect at 0 and 24 h among the four selenocompounds evaluated in this anti-biofilm assay.…”
Section: Inhibition Of Biofilm Growth and Disruption Of Preformed Biomentioning
confidence: 99%
“…At this stage, the underlying mechanism of action of these novel selenoesters against C. glabrata is unknown and more experiments are needed to determine the ultimate mechanism behind the antifungal activity described herein. Selenocompounds and among them, selenoesters, as briefly mentioned in the introduction [31][32][33][34][35][36][37][38][39], have been proven in previous works to be able to exert a wide range of interesting biological activities, both in the anticancer and antimicrobial fields; for example, the modulation of the redox cellular state, scavenging of free radicals, increase of the oxidative stress, induction of apoptosis, and inhibition of efflux pumps, among others [31][32][33][34][35][36][37][38][39]. With the caveat that future works would need to prove it, we could hypothesize that one of several of these mechanisms could explain the observed activities for the symmetrical selenoesters presented in this work.…”
Section: Inhibition Of Biofilm Growth and Disruption Of Preformed Biomentioning
confidence: 99%
See 1 more Smart Citation